Shaping financial futures: exploring the impact of financial literacy, inclusion, and behavior on financial planning in Telkom University's Generation Z - Mayori, Cyndi; Maolana Hidayat, Agus (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Purpose – The research determines the positive and significant influence of Financial Literacy, Financial Inclusion, and Financial Behavior on Financial Planning.Design/methodology/approach – The research methods are quantitative with a descriptive-causal research design. A survey was conducted with 400 samples from the Gen Z student population at Telkom University. The sampling technique used in this research is non-probability sampling (purposive sampling). Data analysis techniques include descriptive analysis and path analysis using Smart-PLS.Findings – The findings indicate that financial literacy has a positive and significant effect on financial inclusion, financial behavior, and financial planning among Gen Z students at Telkom University. Higher financial literacy enables students to use financial services wisely, adopt better financial habits, and achieve effective financial planning. Financial inclusion plays a more significant role than financial behavior in mediating the relationship between financial literacy and financial planning. This highlights the commitment of Telkom University’s Gen Z students to achieving financial goals through accessible financial services and investment products, supporting their efforts to meet financial objectives within targeted timelines. Research limitations/implications – Research findings can play a crucial role in the financial planning of Gen Z students, enabling them to achieve proper and sustainable financial management by enhancing financial literacy, wise financial behavior, and proper utilization of financial products.Practical implications – This research can help Gen Z students to plan their finances by tracking and identifying their levels of financial literacy and financial behavior, as well as their access to financial products. So they can take steps to plan their finances for the future.Originality/value – Previous researchers rarely conducted this study, especially the connection between financial inclusion and financial planning, which positively influences financial planning.